2014
DOI: 10.1016/j.apor.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a hydrodynamic model for a curved, multi-paddle wave tank

Abstract: Obtaining a hydrodynamic model for a wave tank has many benefits, from allowing the useable test zone to be identified, to helping with the tuning of the wavemaker controllers. This paper explores a first-order, boundary element method (BEM) that has been previously proposed for modelling wave tanks, applying the method to a tank with a unique, curved geometry. In a series of experiments, the model is shown to provide a good representation of the wave profile across the tank. Inherent limitations in the method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This set-up is comparable to the taped underwater markers offered by Qualisys, but much lighter, water resistant and buoyant. A preliminary feasibility study showed that such a marker ball can be tracked by the Qualisys system whilst afloat on the surface and subject to wave motions in the University of Edinburgh's Curved Wave Tank [57] and in the FloWave basin, which has a diameter of 25 m and is also located at the University of Edinburgh [58][59][60][61][62][63]. For the experiments, 12 marker balls are added to the water in the circular tank ( Figure 1).…”
Section: Floating Infra-red Reflective Markersmentioning
confidence: 99%
“…This set-up is comparable to the taped underwater markers offered by Qualisys, but much lighter, water resistant and buoyant. A preliminary feasibility study showed that such a marker ball can be tracked by the Qualisys system whilst afloat on the surface and subject to wave motions in the University of Edinburgh's Curved Wave Tank [57] and in the FloWave basin, which has a diameter of 25 m and is also located at the University of Edinburgh [58][59][60][61][62][63]. For the experiments, 12 marker balls are added to the water in the circular tank ( Figure 1).…”
Section: Floating Infra-red Reflective Markersmentioning
confidence: 99%
“…Ohkusu [3] and Kashiwagi [4] proposed a method for indirect estimation of the longitudinal profiles of the radiation and scattering waves generated by a ship model when moving at a constant speed using a single-point wave gauge or an array of such wave gauges aligned longitudinally in a tank. In addition, spatial wave profiles can be obtained by using multiple conventional single-point wave gauges and repeating the measurements after changing the positions of the wave gauges [9][10][11], but this method is very time-consuming. It is thus desirable to be able to measure the spatial wave profiles directly.…”
Section: Introductionmentioning
confidence: 99%